Not a creature was stirring - Haddam, Jane (New York : Bantam Books, 1990)
The Hannaford who made the family fortune called himself a tycoon. The newspapers called him a robber baron. Since the days of Robert Hannaford I, the family has infested Philadelphia society like a disease. The current Hannafords are a clan of embezzlers, gamblers, and fantasy novelists. This Christmas, they have money in their bank accounts, crime in their blood, and murder on their minds. Gregor Demarkian is their reluctant guest. A former FBI agent who quit the agency after his wife$1 (Bs death, he is invited by the Hannaford patriarch to come for dinner at the family mansion. Demarkain arrives just in time to find his host bludgeoned to death in his study and his investigation will lead him to the Hannafords, a family of cold-blooded killers.s
"A Gregor Demarkian holiday mystery."
Keywords: Demarkian, Gregor (Fictitious character); Mystery fiction; Christmas stories